Treatment of infraorbital dark circles in atopic dermatitis with a 2790-nm erbium: yttrium scandium gallium garnet laser: A pilot study. (April 2013) - Park, Kui Young; Oh, In Young; Moon, Nam Ju; Seo, Seong Jun
Abstract Background: Although many Asian atopic patients have orbital darkening symptom and the demand to treat this condition is increasing, little has been reported in the literature on the treatment of infraorbital dark circles in atopic dermatitis. Objective: To evaluate the clinical efficacy and safety of 2790-nm erbium:yttrium scandium gallium garnet (Er:YSGG) laser therapy for reducing infraorbital dark circles in atopic dermatitis patients. Materials and methods: Ten Korean patients over 21 year with mild atopic dermatitis and infraorbital dark circles were enrolled in this study. Patients who need active atopic dermatitis treatments are excluded because of the possibility of aggravation after laser treatment. They were treated for dark circles using a 2790-nm Er:YSGG laser. The treatment parameters were 1.8–2.2 J/cm² fluence, 6-mm spot size, and 0.3-ms pulse width with 10% overlap over the infraorbital areas once with a 4-week interval between treatments. Efficacy was assessed with a quartile grading score ranging from 0 to 5 by a blinded investigator, and the patients also documented their degree of satisfaction with the same grading score. All possible side effects were evaluated. Results: The clinical assessment showed 74.5% (2.7) and 72.5% (2.5) improvements, and the patient satisfaction scale scores improved an average of 74% (2.4) and 71.5% (2.3) at 2 months and 4 months after treatment, respectively. There were no severe side effects or aggravation of atopic dermatitis. Conclusion: Our study suggests that 2790-nm Er:YSGG laser therapy can be effectively and safely used in the treatment of infraorbital dark circles in atopic dermatitis patients.